Respon Tanaman Padi Sawah Terhadap Pemberian Pupuk Organik Cair Jago Tani - Tukidi; Rusnani; Junaidi Ibrahim (Fakultas Pertanian, Universitas Warmadewa, 2022)
The purpose of this research is to know the response of wetland rice production to the application of liquid organic fertilizer of farmer. This research has been done in Suka Jaya Rice Seed Hall of Jembatan Mas village Batang Hari District. The study was conducted from March to August 2014. The experiment was designed with Randomized Block Design (RAK). Organic fertilizer liquid liquid farmer in the test consisted of 6 treatments.dan 4 times replication P0 = Without liquid organic fertilizer farmer, P1 = Organic fertilizer liquid juice farmer as much as 1 cc / liter of water, P2 = organic fertilizer liquid farmer as much as 2 cc / liter of water, P3 = Liquid organic fertilizer for farmer as much as 3 cc / liter of water, P4 = Liquid organic fertilizer farmer as much as 4 cc / liter of water and P5 = Organic liquid farmer farmer as much as 5 cc / liter of water. The results showed that the application of liquid organic fertilizer does not affect the number of productive tillers, weights 1000 grains, but the effect on yield per hectare. The concentration of 3 cc / liter of water gives the best yield reaching 6.61 ton / ha.